Sistem Pelayanan Whatsapp Bot Desa Katemas - Chotimah, Chusnul; Sirojuddin, Didin; Huda, Samsul; Aprilianto , Muchamad Iqbal; Setiawan, Fajar Tri; Haq Tarifuzuri, Ferdinand Izzul; Syifa, Muhammad Miftahusy (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
Public services in Katemas village require innovation to be more optimal in serving the community. with this background, the researcher created an innovation called the WhatsApp Bot Service System. The purpose of creating this system is to make Katemas village services more efficient and optimal. This study uses the Service Learning (SL) method. Seifer defines Service Learning as a teaching approach that integrates community service activities with academic learning objectives. The results of the study are an application that is useful for public services in Katemas village.